Efecto de la aplicación de extractos vegetales en la producción de plántulas de tomate. - Mina Ayala, Yamilex Anahi (2024)
The present investigation was developed in the canton of La Maná, province of Cotopaxi, to analyze the effect of the application of vegetable extracts on the production of tomato seedlings, a completely randomized block design with factorial arrangement A x B was used where A corresponds to the vegetable extracts (coffee and cinnamon) and B corresponds to the dilution doses of the vegetable extracts (1 g, 0.5 g and 0.1 g per liter of water), where morphometric variables evaluated were: seedling height, number of leaves, stem diameter, root length, root length, root weight, root volume, leaf weight, stem weight, root dry weight, leaf dry weight, stem dry weight and dry matter. The results obtained were: plant height, stem weight, and root volume was T3 cinnamon extract 0.1 g/L water, with a value 30.70 cm, 3.19 gr, 3.33%, stem diameter T1 cinnamon extract 1g/L water with 4, 13 cm, in root dry weight, leaf dry weight, stem dry weight and dry matter, the best results obtained with T2 cinnamon extract 0.5 g/L water with 0.81 g, 2.71 g, 1.92 g, 58.12%. In the economic analysis, all the evaluated treatments were profitable at 85% being the highest, the treatment without the application of plant extracts, so the alternative hypothesis is accepted, which mentions that coffee and cinnamon extracts in their different concentrations affect the production of tomato seedlings.